Fundamental Thermal Concepts: An Assessment of University College Students’ Conceptual Understanding of Everyday Perspectives - Villarino, Gil Nicetas Bareng (Universitas Islam Negeri Raden Intan Lampung, 2023)
The phenomenon of the basic thermal concept is a challenging topic in the early learning of thermodynamics. This research investigated students' understanding of basic thermal concepts from an everyday perspective. Nineteen open-ended multiple-choice questions equipped with written justifications for the student's answer choices were used in this study. Items based on everyday perspectives avoiding scientific terminology were given to 244 university students of Leyte Normal University Tacloban City, Leyte, Philippines. This study shows that students' written responses are specific alternative conceptions commonly used. Most of the students could not provide correct reasons for their answers. The results of this study imply that the teaching style in junior and secondary schools in the Philippines may be problematic. These results can be used as a guide for developing appropriate teaching strategies in introductory physics courses, especially on heat.